Long-term bonding efficacy of adhesives containing benzodioxioles as alternative co-initiators - Giana da Silveira LIMA; Andressa Goicochea MOREIRA; Carine Tais Welter MEEREIS; Ginia Brito LIMA; Fernanda Barbosa LEAL; Rafael Ratto de MORAES; Fabrício A OGLIARI; Cesar Liberato PETZHOLD; Evandro PIVA (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This study evaluated the three-year lifespan of the bond to dentin of experimental self-etch adhesives containing benzodioxole derivatives - 1,3-benzodioxole (BDO) and piperonyl alcohol (PA) - as co-initiator alternative to amines. Adhesive resins were formulated using Bis-GMA, TEGDMA, HEMA, camphorquinone and different co-initiators: BDO, PA or ethyl 4-dimethylamino benzoate (EDAB - amine). An experimental self-etch primer was used to complete the two-step, self-etch adhesive system. Clearfil SE Bond (CSE) was used as commercial reference. Bond strength to human dentin was assessed by microtensile bond strength (µTBS) test, and failure mode was classified. Morphology of the dentin bonding interface was assessed via scanning electron microscopy (SEM). Irrespective of the dental adhesives evaluated, µTBS was higher after 24 hours compared with that after 1.5 and 3 years (p ≤ 0.001). However, adhesives with BDO and PA as co-initiators showed significantly higher bond strength than the bonding resin with EDAB (p ≤ 0.002), independent of the time evaluated. The commercial adhesive CSE showed similar bond strength compared with the other groups (p ≥ 0.05). Mixed failures were mainly observed after 24 hours, while adhesive failures were more frequently observed after 1.5 and 3 years. No notable differences in homogeneity and continuity along the bonded interfaces were detected among the materials in the SEM analysis. In conclusion, benzodioxole derivatives are feasible alternative co-initiators to tertiary amine in camphorquinone-based self-etching dental adhesive formulations.